DAMPAK PERTAMBANGAN BATUBARA TERHADAP KUALITAS AIR (KIMIA) SUNGAI MANGGILANG DI JORONG SEBRANG PASAR KANAGARIAN MANGGILANG KABUPATEN 50 KOTA - Gusril M.pd, Henny (LPPM Universitas Muhammadiyah Sumatera Barat, 2017)
This study aims to determine the impact of coal mining on water quality (chemical)Batang Manggilang river in Jorong Sebrang Pasar Kanagarian Manggilang district 50 Kota.Which includes the requirements of chemistry (PH, Suspended, and Iron), based on thedetermination by the Minister of Health no. 492 / Menkes / per / IV / 2010 and GovernmentRegulation of the Republic of Indonesia no. 82 of 2001 on the management of water qualityand control of water pollution.This type of research is an experimental research in the field, and followed bylaboratory analysis. The population of this research is river water of manggilang rod inmanggilang area, district of Pangkalan Regency 50 Kota. While the sample used is acomposite sample. And development instryumen with stage: 1. Collecting research instrumentsin the form of plastic bottles, stationery, calculator and computer. Then performed the testphase of the instrumental and final processing of test results.This type of research is an experimental research in the field, and followed bylaboratory analysis. The population of this research is river water of manggilang rod inmanggilang area, district of Pangkalan Regency 50 Kota. While the sample used is acomposite sample. And development instryumen with stage: 1. Collecting research instrumentsin the form of plastic bottles, stationery, calculator and computer. Then performed the testphase of the instrumental and final processing of test results.